The possible association between Chlamydia pneumoniae infection and asthma. - Al-Zaidi, Mahmood Sh.; Kadhim, Haider S.; Ahmed Shemran, Haider (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Many etiological factors have been implicated in the pathogenesis of Asthma like; viruses, bacteria and Chlamydia pneumoniae. This study focuses on the role of Chlamydia pneumoniae in asthma pathogenesis. Patients and Methods: The detection of Anti-Chlamydia pneumoniae antibodies IgA, IgM and IgG in patients by ELISA, for 35 patients, 18 asthmatic patients, 12 patients with chest infection with no history of asthma, and 5 apparently healthy as control subjects. Results: The results showed that 80% and 70% of the patients were negative for anti- Chlamydia pneumonia antibodies IgA and IgM respectively, while significantly (p<0.05) high number (73%) of patients were positive for IgG, of which significant number (p<0.05) of them, 63% were asthmatic and 36% were non-asthmatic chest infection. Conclusion: this study may support the association between Chlamydia pneumoniae and asthma.